EP-48 Laparoscopy in Emergency Colorectal Surgery: A 7-Year Retrospective Single Centre Cohort Study. (9th August 2022) - Darbyshire, Alexander; Smythe, Rachel; Richardson, John; Khan, Jim; Mercer, Stuart
Abstract: Aim: Colonic diseases requiring urgent resection account for a third of emergency intestinal surgery. Laparoscopy is being increasingly used for emergency surgery, but its role is still being defined. This study describes our centre's experience of adopting a laparoscopic approach for emergency colorectal resection. Method: A retrospective single centre cohort study was performed using local NELA data from January 2014-December 2020. All patients who had a colorectal resection were included, regardless of indication. Patient demographic, operative and in-hospital outcomes were compared for resection type and operative approach. Logistic and linear regression were performed for 30-day mortality and post-operative length of stay. Results: A total 507 colorectal resections were performed. 48.1% were started laparoscopically and 27.6% successfully completed. Attempted laparoscopy rates increased over the study period to over 50% for the last 4 years. Colorectal specialists were more likely to start and complete cases laparoscopically (82.4% and 91.4% vs 60.3% for open). Cases started laparoscopically had significantly lower post-operative length of stay (10.5 vs 16.5 days, p<0.001) and 30-day mortality (6.1% vs 17.9%, p<0.001) than open surgery. Cases completed laparoscopically had a 30-day mortality comparable to elective surgery (2.1%, p<0.001). Patients undergoing laparoscopy were statistically significantly younger, with lower ASA grade and P-POSSUM predicted mortality than open surgery. Conclusion: Laparoscopy can be used effectively and sustainably for emergency colorectal resections in a centre experienced with minimally invasive surgery. This study adds to the body of evidence supporting the safety and efficacy of laparoscopy in the emergency setting.